Intestinal occlusion due to secondary peritoneal hydatidosis - Viola, Huberto; Difilippo, Jose; Goller, Wolfgang (Cirugía del Uruguay, 1974)
A rare case of secundary peritoneal hydatid disease, complicated with obstruction of distal small intestine is reported.